Edukasi Persiapan Persalinan Sehat dan Islami dengan Media Kipas Sebagai Inovasi Komunikasi Efektif Kebidanan dan Solusi Dampak Emisi Karbon di Puskesmas Karang Mekar Banjarmasin Tahun 2024 - Rr. Sri Nuriaty Masdiputri; Noor Anisa; Zahra Sabrina (Lembaga Pengembangan Kinerja Dosen, 2026)
According to the Chair of the Scientific Committee of the International Conference on Indonesia Family Planning and Reproductive Health (ICIFPRH), Indonesia’s Maternal Mortality Rate (MMR) rose in 2023 to 359 per 100,000 live births. In contrast, Indonesia’s MMR target for 2015 was 102 per 100,000 live births. Providing educational materials in the form of fans can help reduce electricity consumption, which is a form of carbon emission reduction. It is hoped that this educational initiative will help pregnant women understand healthy and Islamic childbirth practices over the long term. The objective of this program is to enhance the knowledge of third-trimester pregnant women regarding the importance of healthy and Islamic childbirth while reducing electricity consumption to minimize the impact of carbon emissions. This activity utilized the methods of counseling, question-and-answer sessions, and the distribution of educational fans on childbirth. Results and Conclusions: The results of this activity indicate an increase in knowledge regarding the importance of healthy and Islamic childbirth. There were 32 pregnant women participating in this activity. Among all respondents, the pre-test understanding score was 46%; after the post-test, their understanding increased to 79%, representing a 32% improvement. It is hoped that this community service initiative will be beneficial and help foster a healthy and intelligent generation.